A self-assembled polymer therapeutic for simultaneously enhancing solubility and antimicrobial activity and lowering serum albumin binding of fusidic acid. Issue 17 (22nd November 2021) - Salih, Mohammed; Walvekar, Pavan; Omolo, Calvin A.; Elrashedy, Ahmed A.; Devnarain, Nikita; Fasiku, Victoria; Waddad, Ayman Y.; Mocktar, Chunderika; Govender, Thirumala
Abstract: The global antimicrobial resistance crisis has prompted worldwide efforts to develop new and more efficient antimicrobial compounds, as well as to develop new drug delivery strategies and targeting mechanisms. This study aimed to synthesize a novel polyethylene glycol-fusidic acid (PEG-FA) conjugate for self-assembly into nano-sized structures and explore its potential for simultaneously enhancing aqueous solubility and antibacterial activity of FA. In addition, the ability of PEG-FA to bind to HSA with lower affinity than FA is also investigated. Haemolysis and in vitro cytotoxicity studies confirmed superior biosafety of the novel PEG-FA compared to FA. The water solubility of FA after PEG conjugation was increased by 25-fold compared to the bare drug. PEG-FA nanoparticles displayed particle size, polydispersity index and zeta potential of 149.3 ± 0.21 nm, 0.267 ± 0.01 and 5.97 ± 1.03 mV, respectively. Morphology studies using high-resolution transmission electron microscope revealed a homogenous spherical shape of the PEG-FA nanoparticles. In silico studies showed that Van der Waals forces facilitated PEG-FA self-assembly. HSA binding studies showed that PEG-FA had very weak or no interaction with HSA using in silico molecular docking (-2.93 kcal/mol) and microscale thermophoresis (Kd =14999 ± 1.36 µM), which may prevent bilirubin displacement. Conjugation with PEG did not inhibit the antibacterial activity of FA but rather enhanced it by 2.5-fold against Staphylococcus aureus and methicillin-resistant Staphylococcus aureus, compared to the bare FA. These results show that PEG-FA can simultaneously enhance solubility and antibacterial activity of FA, whilst also reducing binding of HSA to decrease its side effects. Graphical Abstract: UF0001 Communicated by Ramaswamy H. Sarma